Evaluation of Auditory Brainstem Response test in comparison with other standard Behavioral tests results - Ali, Muntaha J.; AL-Said, Wijdan F. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: There has always been a need for valuable measurements that can be used to measure hearing loss degree in patient who cannot responses to the subjective (behavioral) tests. Objectives: to examine the accuracy of the click - Auditory Brain stem Response (ABR) test in estimating the hearing loss degree in comparison with the behavioral tests Free Field (FF) or Pure Tone Audiometry (PTA ). Subjects and method: One hundred twenty one children, with suspected hearing loss, their age between 1-9 year, 51 females and 70 males were examined in this work. Result: The relationship between the hearing loss thresholds using the behavioral tests and click ABR test were variable. The identical ABR results relative to the FF or PTA results in Profound hearing loss were 84 %, and 100 % respectively. But this percentage decreased, starting from the severe hearing loss to normal hearing, it was 57% for PTA and 31% for the FF. Auditory evaluation in children who were suspected of having hearing loss done via the behavioral tests, and click ABR. A comparison has been done between ABR and the Free Field test threshold result in group (1), ABR with Pure Tone Audiometry results in group (2). Conclusion: Click –ABR, (2 – 4 kHz) test cannot be used as the only auditory threshold estimation but as a necessary part of the collective hearing data tests.